Neuraminidase inhibitory activity by compounds isolated from aerial parts of Rhinacanthus nasutus. Issue 17 (2nd September 2018) - Kwak, Hee Jae; Park, SeonJu; Kim, Nanyoung; Yoo, Guijae; Park, Jun Hyung; OH, Youngse; Nhiem, Nguyen Xuan; Kim, Seung Hyun
Abstract: Rhinacanthus nasutus (L.) Kurz (Acanthaceae) is known as traditional medicine for the treatment of various diseases, such as cancer, fungal infections, herpes virus infections and several types of skin diseases in South-East Asian countries. In this study, eight compounds1–8 were isolated from the aerial parts of R. nasutus . The structures of compounds were determined by the spectroscopic methods, including 1D and 2D NMR. The isolated compounds were evaluated for neuraminidase inhibitory activity. Several lignans, 2, 3-bis[(4-hydroxy-3, 5-dimethoxyphenyl)methyl]-1, 4-butanediol (5 ) and 8, 8′-bisdihydrosiringenin glucoside (6 ), significantly inhibited neuraminidase activity, which was comparable to the positive controls, mangiferin and oseltamivir. In addition, a structure-based virtual screening against neuraminidase using bioactive components was demonstrated. Abstract :